Performance Comparison of Heuristic Algorithms for UAV Deployment with Low Power Consumption - Cho, Jun Woo; Kim, Jae Hyun (9th International Conference on Information and Communication Technology Convergence: ICT Convergence Powered by Smart Intelligence, ICTC 2018, 2018)
To minimize power consumption of UAV is one of the big challenges in the UAV deployment. However, it is NP-hard problem due to the pathloss models for Air-to-Ground (A2G) in three-dimensional (3D) area. Therefore many heuristic algorithms are used to solve the UAV deployment. In this paper, we compare the performance of heuristic algorithms for optimal UAV deployment. Among the many heuristic algorithms, we consider Particle Swarm Optimization (PSO), Genetic Algorithm (GA), and Non-hierarchical method which are mostly used for UAV deployment according to each scenario. Performance results show that PSO has better performance than GA in a single UAV case, and Non-hierarchical method has better performance than PSO in multi-UAV case.
Keywords: Hierarchical method; Low-power consumption; Multi UAV; Optimization theory; Path-loss model; Performance comparison; Threedimensional (3-d); Genetic Algorithm; Optimization Theory; Particle Swarm Optimization; Power consumption; UAV